A review of the effectiveness of interventions on medication adherence among hypertension patients - Yew, Sheng Qian; Zulkifley, Nuraisyah Hani; Mohd Nazan, Ahmad Iqmer Nashriq (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
A majority of hypertensive patients will end up suffering uncontrolled hypertension, which is partly due to poor medication adherence. This paper aimed to review a range of interventions that could improve anti-hypertensive medication adherence. Literature search was conducted using PubMed, Scopus, Medline, and Science Direct databases, with publication dates confined to between October 2009 and October 2019. Eventually, only 11 studies were used for this study. It was found that interventions that are based on or include patient education, patient interviews, patient reminders, self-management and behavioural modifications have the potential to improve patients’ adherence to anti-hypertensive therapy. Most successful interventions involve patient reminder, self-management and behavioural intervention.